The Cracking Tradition: Heritage Tourism Potentials of Banton Island and the Challenges Inherent to Indigenous Practices and External Forces - Mapalad, Gina V.; Manzo, Orfelina I.; Fornal, Mae Stella A.; Motin, Borromeo B. (Romblon State University Research Journal, 2021)
Cultural heritage reflects one’s history, tradition, culture, and identity that made up a composite of a nation’s pride. MIMAROPA’s regional development plan noted the Province of Romblon with rich natural attraction and ecotourism potentials. Banton is an island municipality in the northern part of the province of Romblon known for its historical, cultural, and archaeological treasures. Using the emic and etic perspectives, this qualitative research presents Banton’s gifts of history exhibited by archeological artifacts as the niche of heritage tourism and the fading tradition as a lost opportunity to present and future generations. It also discusses the culture, tradition, and practices best known to Bantoanons and the behavioral change influenced by government programs, technology, social media, and outmigration. Lastly, it presents an eye-opener proposition to counter the eroding culture through a holistic strategic planning through consensus building among members of the community.